If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(k + -4) + -3(k + 2) + -13 = -29 Reorder the terms: 4(-4 + k) + -3(k + 2) + -13 = -29 (-4 * 4 + k * 4) + -3(k + 2) + -13 = -29 (-16 + 4k) + -3(k + 2) + -13 = -29 Reorder the terms: -16 + 4k + -3(2 + k) + -13 = -29 -16 + 4k + (2 * -3 + k * -3) + -13 = -29 -16 + 4k + (-6 + -3k) + -13 = -29 Reorder the terms: -16 + -6 + -13 + 4k + -3k = -29 Combine like terms: -16 + -6 = -22 -22 + -13 + 4k + -3k = -29 Combine like terms: -22 + -13 = -35 -35 + 4k + -3k = -29 Combine like terms: 4k + -3k = 1k -35 + 1k = -29 Solving -35 + 1k = -29 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '35' to each side of the equation. -35 + 35 + 1k = -29 + 35 Combine like terms: -35 + 35 = 0 0 + 1k = -29 + 35 1k = -29 + 35 Combine like terms: -29 + 35 = 6 1k = 6 Divide each side by '1'. k = 6 Simplifying k = 6
| 2x+2y=62 | | -210x+6y=330 | | -19a-12+4a=-57 | | -8x^2+14x=12 | | 3n+7-8n=34-11n+21 | | 3(3x+1)=-6 | | 10-5-3x-2x=0 | | -8x^2+14=-12 | | 18x^3-15x^2-7x= | | 2a^2-52-8a=32+a^2-3a | | -3x+2y-(7+x)+(x+7)= | | W=8g+700 | | 3(4+x)=-8(6-x) | | -4a+3-6a-8=15 | | -94=5(2m+2)-2m | | 9(y-1)-(y-5)=10 | | 2Y+4y-8y=36 | | 4p+yr=r-9f | | Y=8g+700 | | 6+4y+10=18 | | 2(4a+3)(a+1)=21 | | 2r-6-7r-9= | | 5(2p-4(p+5))=1 | | 4(3x+2)=200 | | 20x^3-11x^2-9x= | | 4(x+3)-4=8x+104x | | 6+3(b+4)=5b+(b-9) | | 3(1)-5y=0 | | x+8-3=4+3-5 | | 13+5b+7b=5b-7+2b | | (4x+4)(2x+9)= | | 81x^3-36x=0 |